The influence of phylogeny and ecology on root, shoot and plant ionomes of 14 native Brazilian species. Issue 4 (29th August 2019) - Neugebauer, Konrad; El‐Serehy, Hamed A.; George, Timothy S.; McNicol, James W.; Moraes, Milton F.; Sorreano, Maria C. M.; White, Philip J.
Abstract : The ionome is the elemental composition of a living organism, its tissues, cells or cell compartments. The ionomes of roots, stems and leaves of 14 native Brazilian forest species were characterised to examine the relationships between plant and organ ionomes and the phylogenetic and ecological affiliations of species. The null hypothesis that ionomes of Brazilian forest species and their organs do not differ was tested. Concentrations of mineral nutrients in roots, stems and leaves were determined for 14 Brazilian forest species, representing seven angiosperm orders, grown hydroponically in a complete nutrient solution. The 14 species could be differentiated by their ionomes and the partitioning of mineral nutrients between organs. The ionomic differences between the 14 species did not reflect their phylogenetic relationships or successional ecology. Differences between shoot ionomes and root ionomes were greater than differences in the ionome of an organ when compared among genotypes. In conclusion, differences in ionomes of species and their organs reflect a combination of ancient phylogenetic and recent environmental adaptations.